2017
DOI: 10.17794/rgn.2017.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Calibration of Underground Heat Transfer Models Under a Winery Building in a Rural Area

Abstract: Ground temperature and hydrogeological conditions are key parameters for many engineering applications, such as the design of building basements and underground spaces and the assessment of shallow geothermal energy potential. Especially in urban areas, in the very shallow depths, it is diffi cult to fi nd natural undisturbed underground thermal conditions because of anthropic interventions. The assessment of underground behaviour in disturbed conditions will become more and more relevant because of increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…At this stage, a payback analysis can maybe result imprecise since many factors were not considered in the work. Moreover its validity could be strictly limited to the geographical context, nevertheless a first preliminary cost evaluation of the GBHE field installation shows as a homemade installation can return a further remarkable cost savings, in accordance with previous calculations [46]. In fact, several greenhouse farms have available equipment, labour and tools to directly install the baskets and pipes.…”
Section: Scenariosupporting
confidence: 74%
See 1 more Smart Citation
“…At this stage, a payback analysis can maybe result imprecise since many factors were not considered in the work. Moreover its validity could be strictly limited to the geographical context, nevertheless a first preliminary cost evaluation of the GBHE field installation shows as a homemade installation can return a further remarkable cost savings, in accordance with previous calculations [46]. In fact, several greenhouse farms have available equipment, labour and tools to directly install the baskets and pipes.…”
Section: Scenariosupporting
confidence: 74%
“…On the other hand, BGHEs require smaller extensions compared to horizontal probes, due to their conical or cylindrical configuration [39][40][41][42]. Other studies demonstrated that the ground volume involved by the BGHE is affected by seasonal climate variations, meaning that the ground does not reach the "neutral zone", at constant temperature, usually found at depths of 10 m and more, varying based on hydrogeological conditions [43][44][45][46]. Therefore, the adoption of BGHE prevents the rapid heat reintegration after thermal exchange between the probes and the ground, thus decreasing the geothermal system performance [47].…”
Section: Introductionmentioning
confidence: 99%
“…For this, the physical exergy of the incoming air is calculated using (9), while (10) is not needed here since the absolute humidity of the incoming air is unchanged at ω = ω°. Thus, the exergy efficiency for HP integration with EAHR becomes, based on (11):…”
Section: Cases C and D: Ground Or Air Source Hp 75% Exhaust Air Heat ...mentioning
confidence: 99%
“…For the low temperature heat sources the air-source heat pump used ambient air with temperature varying between -20.0 and 32.8°C, with an hour-based annual average value 7.32 °C. This 7.32°C is taken as the constant low temperature heat source temperature for the ground-source heat pump, located at ~ 100 m depth [11].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring ground temperature is an important issue in the shallow geothermal sector, both for research and professional purposes. Due to technology advancements and a decrease in costs, electronic measurement, registration and data transmission systems have been widely applied for many purposes, such as the validation of models (Tinti et al, 2017;Badenes et al, 2017), the control of system behaviour and effi ciencies (Montagud et al, 2011) and the management of the resource by local and regional environmental authorities (Hähnlein et al, 2013).…”
Section: Introductionmentioning
confidence: 99%